UNDERSTANDING THE ROLE OF THE GENES EOMESODERMIN, INTERLEUKIN-6 AND SOX17 IN THE PRE-GASTRULATION PIG EMBRYO - Wood, Liam (2019)
The mechanisms of early embryonic development in large mammals is still largely unknown. These mechanisms have been well defined in the mouse embryo. However, recent literature has found striking differences between early development in mice and larger mammals such as humans, pigs and monkeys. Since human embryos cannot be used for ethical reasons, porcine embryos were used in to establish a model of early development in large mammals. In this thesis I sought to investigate the roles of 2 genes, Interleukin-6 (IL-6) and Eomesodermin (EOMES), in the early development of the pig embryo. These genes were chosen due to preliminary data which highlights different expression patterns between mice and pigs. Based on this I drew the hypothesis that the function of IL-6 and EOMES in the pig embryo differs to that of the mouse embryo. To gain an insight into the role of IL 6, porcine embryos were cultured in the presence of IL-6 and an IL-6 inhibitor. A method of IL-6 knockout by CRISPR-Cas9 genome editing was also developed. Considering that EOMES expression in the embryo is outside the scope of in vitro study a CRISPR based method was designed with a view of generating high knockout efficiencies prior to an in vivo study. The study found that IL-6 has a trophic effect on the trophectoderm lineage of in vitro parthenogenetically activated pig embryos, but does not play a role in pluripotency as hypothesised. Additionally Leukaemia inhibitory factor has a negative effect on the expansion of the trophectoderm lineage in vitro. Furthermore, genome editing via CRISPR-Cas9 methods were somewhat efficient at creating EOMES-null embryos, however, further optimisation is required in order to increase editing efficiency for future studies.